2018
DOI: 10.1093/ntr/nty185
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and Reciprocal Relationships Between Psychological Well-Being and Smoking

Abstract: Findings warrant further exploration of the relationships between PWB and smoking, and support the incorporation of PWB-boosting components into existing treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 60 publications
2
20
0
1
Order By: Relevance
“…In another study using structural equation modelling, non-smoking predicted measures of subjective well-being and vice versa in older adults (mean age = 64 years) with a follow-up of four years [17]. The highest path coefficient was observed for smoking status predicting subsequent smoking (1.77), which is in line with our study showing high longitudinal correlations of health behaviors and smoking having the highest value of these.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…In another study using structural equation modelling, non-smoking predicted measures of subjective well-being and vice versa in older adults (mean age = 64 years) with a follow-up of four years [17]. The highest path coefficient was observed for smoking status predicting subsequent smoking (1.77), which is in line with our study showing high longitudinal correlations of health behaviors and smoking having the highest value of these.…”
Section: Plos Onesupporting
confidence: 88%
“…It enables a more detailed analysis of individual components of health behavior and subjective well-being as their distinctive impacts on the latent variable are investigated. In a study using structural equation modeling [17], the effects of smoking on subsequent lower life satisfaction, lower optimism, and less positive affect (path coefficients = 0.10-0.025) were stronger than the effects in the opposite direction (path coefficients = 0.04-0.08) in a four-year follow-up on older adults (mean age = 64 years). The cross-sectional associations between smoking and subjective well-being at baseline were also statistically significant (path coefficients = 0.04-0.05).…”
Section: Introductionmentioning
confidence: 98%
“…[ 45 , 50 , 51 , 54 , 56 , 57 , 60 , 61 , 65 , 66 , 72 74 , 80 , 83 , 91 , 94 , 96 , 101 , 105 , 108 , 111 , 117 , 124 , 126 , 127 , 129 , 130 ]…”
Section: Resultsunclassified
“…Previously, heavy alcohol consumption predicted poorer life satisfaction during a 15-year follow-up with the same, but categorized, life satisfaction scale as used here [ 14 ]. Another study [ 13 ] concluded by structural equation modeling that smoking predicted significantly poorer life satisfaction 4 years later. Further, the study by Mujcic and Oswald [ 11 ] explored the association between initial fruit and vegetable consumption and later life satisfaction in a 2-year follow-up adjusting for exercise, smoking, alcohol consumption and eating patterns; consumption of fruit and vegetables predicted subsequent life satisfaction and an average increase of 0.24 in life satisfaction (range: 0–10) was observed when the consumption of fruits and vegetables was increased by eight portions a day.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy dietary patterns have been positively associated with good life satisfaction on a day-to-day basis [ 9 , 10 ], have improved life satisfaction if changed in a favorable direction even when adjusted for other health behaviors [ 11 , 12 ], and have predicted better life satisfaction in a 2-year follow-up [ 11 ]. Furthermore, being a smoker predicted poorer life satisfaction 4 years later [ 13 ], and high alcohol consumption poorer life satisfaction during a 15-year follow-up [ 14 ]. In addition, physical activity has shown a positive association with life satisfaction on a day-to-day basis [ 15 ] and increased physical activity has been shown to improve life satisfaction [ 16 ].…”
Section: Introductionmentioning
confidence: 99%